Distortion product otoacoustic emissions in geriatric dogs. (October 2016) - Strain, G.M.; Rosado Martinez, A.J.; McGee, K.A.; McMillan, C.L.
Highlights: Distortion product otoacoustic emissions (DPOAEs) can be used for frequency-specific hearing loss assessment in dogs. Dogs classified as geriatric had significant hearing losses that were greater for middle and high frequencies. There was no significant relationship between age and DPOAE response reduction. Clinically significant hearing losses pre-date ages considered to be geriatric. Abstract: Recordings of distortion product otoacoustic emissions (DPOAE) were taken from 28 geriatric dogs aged 12.2 ± 2.2 years and 15 control dogs aged 5.9 ± 3.0 years (mean ± standard deviation) to demonstrate frequency-specific changes in cochlear responses. Recordings were performed for primary frequencies of 2–12 kHz in 2 kHz increments. Brainstem auditory evoked response (BAER) recordings were also made from geriatric dogs for comparison with DPOAE responses. Significant decreases in DPOAE response amplitudes were observed at frequencies of 6–12 kHz in geriatric dogs compared to control dogs, reflecting loss of cochlear outer hair cells along the length of the cochlea. Significant decreases in response amplitudes were not seen at frequencies of 2 or 4 kHz. Decreases in BAER response amplitudes subjectively paralleled the depressed DPOAE amplitudes. No significant linear regression relationships were found for DPOAE response amplitude vs. age despite the progressive nature of age-related hearing loss. The reductions in response at all frequencies starting at the age where dogs are considered geriatric indicate that age-related hearing loss begins earlier in the life span. DPOAE recordings provide a means to assess cochlear function across different portions of the auditory spectrum for assessing hearing loss associated with aging, and potentially for losses from other causes of decreased auditory function.